Expression of Communicative and Organizational Abilities in Representatives of Dance Sport and Other Dance Styles (Adolescents) (Baltic Journal of Sport and Health Sciences, 2022)
The aim of the research. To reveal the expression of communicative and organizational abilities in representatives of dance sport and other dance styles (ballet, street, modern, national, lindy hop) (adolescents).Methods. The research involved 50 adolescents (28 girls and 22 boys) that attended dance sport, and 50 participants (30 girls and 20 boys) that attended dance of other styles (ballet, street, modern, national, lindy hop). The age of the research participants was 12–14 years. The questionnaire was compiled according to the methodology of Fedorishin and Sinyavskiy (2017), aiming to assess communicative and organizational abilities. The abilities of the dancers assessed according to this methodology were classified as “very low”, “low”, “average”, “upper average” and “high” levels.Results. After assessing the communicative abilities in the research participants of dance sport in the aspect of gender, we determined that the communicative abilities in most girls (36.42 per cent) and boys (37.50 per cent) were high. After assessing their organizational abilities, it was determined the organizational abilities in most researched (37.48 per cent of the boys and 45.49 per cent of the girls) matched to the low level. Among the research participants of other dance styles, the level of communicative abilities was high in 30.00 per cent of the boys and 24.98 per cent of the girls. After assessing the organizational abilities of this group of dancers, it was determined the low level of organizational abilities was most expressed, matching 30.24 per cent of the boys and 64.86 per cent of the girls.Conclusions. After assessing the adolescents that attended dance sport or dance of other styles, it was determined the level of communicative and organizational abilities among the research participants of those groups did not differ statistically significantly.Key words: dance sport, other dance styles, communicative abilities, organizational abilities.